Achromobacter xylosoxidans bacteremia: clinical and microbiological features in a 10-year case series - Barragán, Edgar Pérez (Rev Esp Quimioter, 2018)
OBJECTIVE: The treatment of Achromobacter xylosoxidans bacteremia is challenged by antimicrobial resistance and the paucity of data. We aimed at offering a contemporary description of this uncommon entity. PATIENTS AND METHODS: Retrospective case series of 13 episodes of A. xylosoxidans bacteremia diagnosed over a 10-year period (November 2007 to May 2017) in our tertiary care center. RESULTS: Solid organ cancer and heart failure were the most common comorbidities (4/13 [30.7%]). All but one episodes were hospital-acquired. Most patients had received previous antibiotic therapy (7/13 [53.8%]) and had a central venous catheter in place (6/13 [46.1%]). Primary and intravascular catheter were the most common sources (4/13 [30.7%] each). Meropenem was the agent with best in vitro activity (92.3% [12/13] of susceptible isolates). All-cause 30-day mortality (overall 23.1%) was higher in patients with primary bacteremia (50.0% vs. 11.1%; P-value=0.203) and prior chemotherapy (66.7% vs. 10.0%; P-value=0.108). CONCLUSIONS: Bacteremia due to A. xylosoxidans constitutes a serious infection among immunocompromised hosts. Carbapenem-based therapy may be appropriate in most cases.